Symposium 1: Networked Identities – Understanding Different Types of Social Organisation and Movements Between Strong and Weak Ties In Networked Environments - Ryberg, Thomas; Larsen, Malene Charlotte (Proceedings of the International Conference on Networked Learning, 2006)
In this article we take up a critique of the concept of Communities of Practice voiced by several authors, who suggest that network may provide a better metaphor to understand social forms of organisation and learning. This critique we situate within a broader theoretical movement in socio-cultural learning theories. From this we identify some theoretical and analytical challenges to the network metaphor, which we explore and elaborate through an analysis of a Danish social networking site.